2020
DOI: 10.1016/j.jaapos.2020.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Ocular manifestations and viral shedding in tears of pediatric patients with coronavirus disease 2019: a preliminary report

Abstract: PURPOSETo evaluate ocular manifestations and severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) prevalence in the tears of children with coronavirus disease 2019 . METHODSA total of 27 pediatric patients with confirmed COVID-19 infection hospitalized from March 16 to April 15, 2020, at the Bambino Ges u Children's Hospital were enrolled in the study. At admission, all patients showed ocular manifestations. Reverse transcriptase-polymerase chain reaction from nasopharyngeal and conjunctival swabs were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
84
0
8

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 67 publications
(93 citation statements)
references
References 18 publications
1
84
0
8
Order By: Relevance
“…One of the major conclusions which one can make from this systematic review is that the prevalence of ocular symptoms and signs is low and that conjunctivitis is a relatively rare occurrence. In this review, this prevalence ranges from 0 to 31.58% [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. This is in keeping with a previous large study from China which reported that nine patients (0.82%) out of 1099 laboratory-confirmed COVID-19 patients experienced conjunctival congestion [23].…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…One of the major conclusions which one can make from this systematic review is that the prevalence of ocular symptoms and signs is low and that conjunctivitis is a relatively rare occurrence. In this review, this prevalence ranges from 0 to 31.58% [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. This is in keeping with a previous large study from China which reported that nine patients (0.82%) out of 1099 laboratory-confirmed COVID-19 patients experienced conjunctival congestion [23].…”
Section: Resultssupporting
confidence: 86%
“…It was also reported in a univariate analysis that patients with more severe pneumonia were more likely to experience ocular symptoms and signs, with higher levels of white blood cells, neutrophils, procalcitonin, C-reactive protein, and lactate dehydrogenase compared with patients without ocular symptoms and signs [8]. The ocular manifestations and prevalence of SARS-CoV-2 in 27 children were evaluated by Valente et al in a prospective case series [12]. Out of 27 patients, ocular symptoms and signs consistent with mild viral conjunctivitis including conjunctival injection and secretion were observed in four patients (14.81%).…”
Section: Summary Of Study Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…The clinical manifestations of SARS-CoV-2 infection, or Coronavirus disease 2019 (COVID- 19), range from asymptomatic or subclinical infections, to acute viral pneumonitis with respiratory failure and/or multi-organ dysfunction [5][6][7]. Case reports and small retrospective cohorts of conjunctivitis as a presenting feature of SARS-CoV-2 infection emerged since the early phase of the pandemic.…”
Section: Introductionmentioning
confidence: 99%